2017
DOI: 10.5812/archcid.13306
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Quantitative Assay of HBsAg and Hepatitis B Virus DNA Levels Among Chronic HBV Patients Attending Pathologist Lancet Laboratory in Nairobi, Kenya

Abstract: Background: Hepatitis B Virus (HBV) viral load measurements is recommended for diagnosis and monitoring of patients on treatment for Chronic Hepatitis B (CHB). However, these diagnostic techniques are molecular-based and expensive and unavailable to majority of the Kenyan population. Quantitation of hepatitis B surface antigen (HBsAg) by automated chemiluminescent microparticle immunoassay has been proposed as a surrogate marker. Objectives: This study showed the correlation between HBsAg and HBV DNA levels am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
3
0
0
Order By: Relevance
“…This suggests that HBsAg quantitation may not be an effective alternative to serum HBV-DNA quantification in hepatitis B virus infected patients. This finding is similar to the report of Mathia et al, [26]. HBVDNA, is the template for gene transcription and replication and level is the most important and most direct etiological evidence for HBV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that HBsAg quantitation may not be an effective alternative to serum HBV-DNA quantification in hepatitis B virus infected patients. This finding is similar to the report of Mathia et al, [26]. HBVDNA, is the template for gene transcription and replication and level is the most important and most direct etiological evidence for HBV.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with that of Yewande et al, [27]. The children (<20) and the aged (>50) have less exposure to risky behaviours than the middle aged (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 89%
“…The current study showed that not all HBsAg seropositive patients were positive for HBV DNA detection by RT-PCR, which was agreed with observations reported by a study done in Nairobi (Kenya) in 2017 by Mathai et al [27]. They reported that the seropositive results of HBsAg and HBV DNA detection are totally different, and none of ELISA and RT-PCR cannot be alternative for each other [28].…”
Section: Discussionsupporting
confidence: 92%
“…An earlier study [ 11 , 18 ] supports this observation. In another study, no significant correlation was observed between qHBsAg and HBV-DNA in both HBeAg-positive and negative patients (r = 0.309, p = 0.093; r = 0.065, p = 0.443; respectively) [ 19 ]. On the contrary, an earlier Korean study revealed a weak but significant positive correlation between qHBsAg and HBV-DNA; however, this relationship was not observed during the late replicative phases of CHB infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%